Attitudes towards mental illness in American Evangelical communities, supernaturalism, and stigmatisation - Freeman, Nahanni (Mental health, religion & culture, 2020)
Social-cognitive variables and religious attributions regarding mental illness were examined with a homogeneous sample of 180 American Evangelical Christians, using a novel tool and the Mental Health Knowledge Scale (MAKS). In the first trial, participants were randomly assigned to one of two Bible verse priming conditions, which made salient willpower, faith and anxiety-reduction or the suffering Christ. Priming effects revealed that those exposed to the willpower-faith admonishment condition showed lower stigma on the MAKS and stronger condition recognition scores. Participants who endorsed unilateral religious causes and solutions to mental illness also presented with less knowledge about mental health disorders and lower condition recognition, but the latter was unrelated to positive views regarding religiously-informed interventions. Females showed higher levels of condition recognition and fewer stigmatising attitudes.